Health-related quality of life (SF-36) in back pain: a population-based study, Campinas, São Paulo State, Brazil - Aparecida Mari Iguti; Margareth Guimarães; Marilisa Berti Azevedo Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Our study aimed at assessing back pain impact over health-related quality of life (HRQoL). This is a cross-sectional population-based study that analyzed 1,192 adults. The dependent variables were the SF-36 scales and the main independent variables was back pain characterized by location, number of back pain region, intensity, frequency and limitations. Simple and multiple linear regression models were performed to estimate the crude and adjusted beta-coefficients (gender, age, schooling and co-morbidity conditions). Back pain prevalence were 35.4%. For HRQoL, comparing people with/without back pain, we found weak associations for the physical component (β = -3.6). However, strong associations were found for physical component (β = -12.4) when there were concomitant pain in cervical, dorsal and lumbar sites and also associations with mental health scales. Daily pain was associated with physical (β = -6.8) and mental (β = -2.7) components. Important impact on physical componente summary was found for intense/very intense pain (β = -7.9) and pain with severe limitation (β = -11.5). The impacts over HRQoL were strong when back pain was followed by (1) multiple back sites, (2) with pain in mental componente summary, (3) daily complaints, (4) very intense pain and (5) severe limitations; these results have revealed the importance to measure specific factors related to back pain.